Теоретичні положення обґрунтування сутності та особливостей розвитку агробізнесу. - Kyfyak, Viktoria (Науковий вісник Полісся, 2024)
Анотація. У статті розглянуто теоретичні положення щодо обґрунтування сутності аграрного бізнесу як виду підприємницької діяльності, визначення особливостей її здійснення в ринкових умовах. Це було реалізовано через дослідження змісту категорії «бізнес», аналізу наукових праць, в яких розглядалася ця категорія, що дозволило обґрунтувати специфічні риси бізнесу як економічної діяльності. Також у статті систематизовано основні наукові підходи до розуміння сутності аграрного бізнесу. У підсумку на основі результатів такої систематизації виокремлено окремі підходи до розгляду цієї підприємницької діяльності (економічний, галузевий, системний, правовий, інституційний, соціальний) та конкретизовано особливості її здійснення
THEORETICAL PROVISIONS ON SUBSTANTIATING THE ESSENCE AND PECULIARITIES OF THE AGRIBUSINESS DEVELOPMENT Abstract. In todays’ environment, agribusiness plays one of the most important roles in development the national economy of different countries. The development of this business is directly related to the production of food for citizens, which helps ensuring necessary level of food security. In addition, its development allows for more efficient use of the existing natural potential of countries and thereby contributes to the intensified economic activity in the country. Accordingly, theoretical and applied provisions in the agribusiness development are relevant today. In the article, theoretical provisions on substantiation of the agribusiness essence as a type of the entrepreneurial activity are considered. This was done based on the study of the business essence as a type of the economic activity, substantiation of the specific features of this activity, and its implementation in the market conditions of the national economy. In the article, considerable attention is also paid to the study of the approaches available in the scientific literature to the essence of the agribusiness. This made it possible to identify the following approaches, to systematize them, and, as a result, to identify the main basic approaches that are most often used by scientists when considering the content of the agribusiness. These approaches include the following ones: economic, sectorial, systematic, legal, institutional and sociall. A detailed consideration of these approaches allowed the author to propose its own approach to understanding the content of the agribusiness, namely to consider it as am sector of the economy consisting of separate areas of the economic activity within which economic entities produce, process, sell agricultural products, create agro-industrial products to generate profit and additional social outcomes. In other words, within the article, the macro approach to the essence of the agribusiness is used. As a result, it also allowed us to substantiate the main features of the economic activity related to the functioning of the agribusiness sector. In the course of the study it was found out that institutional factors play a significant role in the agribusiness development today, namely: available state support and effective activity of public authorities and local self-government bodies in regulating the economic activity within the national economy sector
Keywords: Ключові слова: агробізнес, бізнес, сільське господарство, агропромислове підприємство, аграрна галузь, національна економіка